SOME FEATURES OF MUSLIM LAW: NEW TRENDS IN ITS DEVELOPMENT - Seitakhmetova N.L.; Kussainov D.U.; Ayupova Z.K. (Scientific Journal of Pedagogy and Economics, 2021)
The essence of the integration process in Muslim law has expressed in the enlargement and consolidation of the social relations through the definite points, objects of the concentration of the tension and gradual incorporation of the human being into the community with the system of the relations, with the global order, based on the balance of the regulating influence of the legal systems of the different states and synchronic of the regulating behavior in the different societies. The movable force of the process of the integration is inside the system of the society and social relations in the world scale. Muslim law is an Islamic doctrine about the rules of behavior of the Muslims. The main content of Muslim law is the rules of behavior of believers, that follow from the Sharia and sanctions for non-compliance with these regulations. It was formed in the VII-X centuries in the connection with the formation of the Muslim state - Caliphate. The formation of Muslim law was caused, on the one hand, by the need to bring the actual law in line with the religious norms of Islam, on the other hand, by the need to regulate public relations on the principles, based on the religious and ethical teachings of Islam.